Elaboração de um guia para registro de medicamentos ANTI-TNF-α como produtos biossimilares no Brasil - Oliveira, Michelle Werneck (2019)
In order for a biological product to be marketedas a medicine in our country, it must undergo an analysis regarding the quality, efficacy and safety aspects for the granting of the marketing authorizationin Brazil by the BrazilianHealth Surveillance Agency (Anvisa). Among the various biological products in the pharmaceutical market, those used in the treatment of rheumatoid arthritis (RA) have received important spotlight; being the development of disease-modifying anti-rheumatic drugs (DMARDs) considered as one of the most relevant advances in rheumatoid arthritis therapy. In patients who have been failed traditional therapy used for the treatment of RA, treatment with the biologically active anti-TNF-alpha DMARDs currently available on the market is initiated.The high cost of these biological products and their increasing use in the treatment of RA as well as other diseases for which they are indicated; coupled with the need to reduce pharmaceutical expenditures for better control and cost-effectiveness of public health expenditures, provide a considerable boost to the emerging market of similar to anti-TNF-αbiological products.The authorization of a biosimilar drug in Brazil, in addition to complying with RDC n° 55/2010, must comply with the requirements established in international guidelines of globally recognized entities; and considering the complexity of biological products, it is extremely important to develop specific guides that provide guidance to developers of biosimilars.In this sense, the aimed of this study was to establish sanitary guidelines through the preparation of a guide for biological drugs inhibiting tumor necrosis factor (Anti-TNF-α) as biosimilar products in Brazil.For this, a descriptive quantitative research was carried out, with an overview of the regulatory processes, which aims to allow an adequate orientation of the processes involving the development and registration of this group of product, with non-clinical and clinical requirements for the registration of anti-TNF-α action biosimilarsin Brazil, in whichthe safety and efficacy of medicines can be evaluated in a standardized and even more efficient way at Anvisa. It is believed that the proposed work will provide guidance for the development of these biosimilar products and standardization of registrationprocesses in Brazil.